Implementing Strategies to Foster Vocabulary Acquisition : Gains and Challenges (2021)
ABSTRACT: This research study was carried out in a public institution in Medellin named Fundadores. It aimed to explore the gains and challenges students experienced while using vocabulary acquisition strategies. Data analysis suggests that students were able to build vocabulary and recognize some sentence patterns. To explore these gains and challenges, recordings, interviews, and reflections were used.